Factors associated with intimacy and sexuality among young women with multiple sclerosis - Mohammadi, Khadijeh (Reprod Health, 2020)
BACKGROUND: Patients with multiple sclerosis (MS) especially those with younger age experience an alteration in physiological and emotional lifestyle that can affect intimacy and sexuality. The aim of this study was to determine demographic and disease related determinants of intimacy and sexuality in young women with MS. METHODS: This was a cross sectional study carried out in Tehran, Iran. A convenience sample of young women aged ≤35 years old with MS attending to outpatient clinics in a teaching hospital affiliated to Tehran University of Medical Sciences was entered into the study. The Multiple Sclerosis Intimacy and Sexuality Questionnaire-19 (MSISQ-19) was used to evaluate how the disease influences sexual function and satisfaction in these patients. Multivariable analysis using hierarchical method was performed to identify variables that are associated with intimacy and sexuality. RESULTS: In total 117 young women with confirmed diagnosis of MS were included in the study. Participants mean was 25.7 (SD = 8.07) years. A multivariable hierarchical regression analysis was performed using demographic variables entered in step one, relevant neurological variables in step two, and psychological variables in step three. Furthermore, we loaded antidepressant use in the last step. Overall, the seven variables accounted for 39% of total variance observed for the MSISQ score (P < 0.001). At step one the demographic variables accounted for 13% of the variance in the MSISQ score (P < 0.001). At step two the inclusion of relevant neurological variables increased the R(2) significantly and explained 27% of variance for the MSISQ (P < 0.001). However in the third step the inclusion of psychological factors increased R(2) significantly (adjusted R(2) increased to 0.39, P < 0.001). CONCLUSIONS: The findings indicated that psychological, disease-related and demographic factors (education and employment status) contributed to intimacy and sexuality in young women with multiple sclerosis. Appropriate interventions, especially psychological interventions, appear to be essential immediately following a definite MS diagnosis in young women.